2018
DOI: 10.1002/ijc.31306
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate in drinking water and colorectal cancer risk: A nationwide population‐based cohort study

Abstract: Nitrate in drinking water may increase risk of colorectal cancer due to endogenous transformation into carcinogenic N-nitroso compounds. Epidemiological studies are few and often challenged by their limited ability of estimating long-term exposure on a detailed individual level. We exploited population-based health register data, linked in time and space with longitudinal drinking water quality data, on an individual level to study the association between long-term drinking water nitrate exposure and colorecta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
145
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 261 publications
(149 citation statements)
references
References 25 publications
1
145
0
3
Order By: Relevance
“…In studies of pit latrine impacts on groundwater quality, NO 3 − is the most commonly detected pollutant (Graham and Polizzotto 2013). Though safe levels of NO 3 − for humans in drinking water are still debated (Schullehner et al 2018), it is clear that this is a critical and widespread pollutant. Elevated concentrations of NO 3 − have been found in arid environments, including the Kalahari Desert, where it is believed to be the product of the decomposition of ancient vegetation deposits (Heaton et al 1983;Stadler et al 2012;Stone and Edmunds 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In studies of pit latrine impacts on groundwater quality, NO 3 − is the most commonly detected pollutant (Graham and Polizzotto 2013). Though safe levels of NO 3 − for humans in drinking water are still debated (Schullehner et al 2018), it is clear that this is a critical and widespread pollutant. Elevated concentrations of NO 3 − have been found in arid environments, including the Kalahari Desert, where it is believed to be the product of the decomposition of ancient vegetation deposits (Heaton et al 1983;Stadler et al 2012;Stone and Edmunds 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In a large population-based study in Denmark, Schullehner et al reported a significantly increased risk of CRC among individuals exposed to nitrates in drinking water as low as 3.87 mg/ L. This finding is noteworthy because 3.87 mg/L is an order of magnitude lower than the Danish drinking water standard for nitrates, 50 mg/L. [25] The nitrate standard for public drinking water in the USA is 10 mg/L (https://www.wqa.org/Portals/0/ Technical/Technical%20Fact%20Sheets/2014_NitrateNitrite. pdf).…”
Section: Discussionmentioning
confidence: 98%
“…Specifically, elevated nitrate levels in water lead to the formation of potentially carcinogenic N-nitrosamines (van Maanen et al, 1996). In some studies, the long-term consumption of nitrate in drinking water has been positively associated with a higher risk for non-Hodgkin's lymphoma, stomach, colorectal, bladder, breast, and ovarian cancers, and thyroid disease (Espejo-Herrera et al, 2016;Fachiroh et al, 2017;Gulis et al, 2002;Inoue-Choi et al, 2013;Jones et al, 2016;Schullehner et al, 2018;Ward et al, 2018;Weyer et al, 2001), although findings over time have not been consistent. Phosphorus is not directly toxic to human beings, but it is often the limiting nutrient in aquatic ecosystems (FAO et al, 2006) and changes in concentration can severely alter ecosystem functions.…”
Section: Chemical Pollutantsmentioning
confidence: 99%